REKONTRUKSI PASAL 7 AYAT (1), UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK, BERBASIS PRINSIP-PRINSIP INDIVIDUALISASI PIDANA DALAM HUKUM ISLAM - Maemunah, Maemunah (Universitas Wiralodra, 2020)
Children are a trust and gift from God who has dignity and dignity as a whole human being. In order to safeguard his dignity, the child is entitled to special protection, especially legal protection in the justice system. In realizing the maximum child protection, requires a policy that supports the realization of maximum protection, with the issuance of Law Number 11 Year 2012, concerning the Juvenile Justice System. This is done because Indonesia as a State Party in the Convection of children's rights governing the principle of legal protection against children have an obligation to provide special protection for children in conflict with the law. In Article 7 Paragraphs 1 and 2 of the Law on the Juvenile Justice System, article 7 (1) At the level of investigation, prosecution and examination of cases of children in the district court must be endeavored Diversion, (2) Diversion as meant in paragraph (1) is carried out in the case of acts crimes committed: (a) are threatened with imprisonment of less than 7 (seven) years and (b) do not constitute repeat offenses. This study intended to examine and analyze the form of legal construction of the Juvenile Justice System specifically implementing diversion for victims with demands of less than 7 years. The research method uses a statutory approach, a case approach, and a comparative approach to the number of cases by reviewing and analyzing legislation, journals, cases, data and direct interviews. According to the results of the study, it is found that the implementation of legal penal system of the Juvenile Justice System (1) child cases is increasing, (2) diversion is carried out since the investigation up to the court, and there are still many that are done at a higher level, (3) have an understanding, that diversion must be sought, has a meaning that can be done at various levels so that diversion occurs at several levels, and often occurs at the Court level.